Islamic law and society - Yakar, Emine Enise, author.
1 online resource (x, 302 pages).
Keywords: "This book places context at the core of the Islamic mechanism of ifta' to better understand the process of issuing fatwas in Muslim countries thus highlighting the gap between context and contemporaneity, on one hand, and the common perception of Islamic Law as frozen in time. The practice of iftā' is one of the most important mechanisms of Islamic law that keeps Islamic thought about ethical and legal issues in harmony with the demands, exigencies and developments of time. This book highlights the complexity of the practice of Islamic legal opinion-making by contemporary institutions and reveals the interaction between Islamic legal methodologies and different environmental contexts. The work provides a textual analysis of fatwās issued by the Dār al-Iftā' in Saudi Arabia and the Diyanet in Turkey that include wide-ranging issues. It presents an analysis and comparison of similar fatwās produced by the two institutions from the methodological and contextual standpoints. This demonstrates the existence of complex and diverse ideas around similar issues within contemporary Islamic legal opinions that is further complicated by the influence of international social, political, cultural and ideological contexts. The book thus unveils a more complicated range of interactive constituents in the process of the practice of iftā' and its outputs, fatwās"--